Food and Power in Sixteenth-Century Ireland: Studying Household Accounts from Dublin Castle. (February 2023) - Taverner, Charlie; Flavin, Susan
Abstract: Studying the food practices of one vast and prominent Irish household reveals a complex history of consumption, status, and power in sixteenth-century Europe. This article is a close analysis of the little studied but unusually detailed household accounts of William Fitzwilliam, lord deputy of Ireland during 1572–5 and 1588–94. It first discusses how early modern historians have probed similar records and how these examples can be interpreted. The following sections examine the specific foods consumed at Dublin Castle and the high cost, distinctive rhythms, and deep symbolism of grand-scale dining at the viceroy's primary residence. This study of the everyday life of one of the most powerful officeholders in England and Ireland offers fresh perspectives on the region's political history. It also adds to the burgeoning study of Irish consumption, showing that the country was connected to continental developments. More than an Irish story, this article offers evidence of Europe-wide changes, like the elaboration of courtly cuisine and the shifting associations of foodstuffs, and how these changes were filtered through local circumstances. It suggests too how historians can make productive use of household accounts, sources well suited to comparison and combination with other disciplinary approaches.